Dimension theory and fuzzy topological spaces - S. S. Benchalli; B. M. Ittanagi; P. G. Patil (International Journal of Mathematics and Mathematical Sciences)
J. M. Aarts introduced and studied a new dimension function, Hind, in 1975 and obtained several results on this function. In this paper, a new local inductive dimension function called local huge inductive dimension function denoted by locHind is introduced and studied. Furthermore, an effort is made to introduce and study dimension functions for fuzzy topological spaces. It has been possible to introduce and study the small inductive dimension function indfX and large inductive dimension function indfX for a fuzzy topological space X.